Patriotism And Armenian Statehood In The Norms Of Armenian Law - Hovsepyan, Aghvan (Տիգրան Մեծ)
The purpose of the article is to study and present the sources of Armenian law that contain provisions on patriotism and Armenian statehood.To achieve this goal, our task is to investigate the legal and patriotic labour standards of Hakob and Shahamir Shahamirian‘s Girk Anvanial Vorogayt Parats (Snare of Glory). It is no secret that the work ―Vorogayt Parats‖ is one of the most important documents of Armenian law, which for the first time in the reality of Armenia presents a holistic and orderly system of norms of various branches of law.As a result of the research were applied both scientific (analysis, the principle of historicity) and spe-cial (comparative-legal) methods. The study of the above mentioned legal and patriotic norms gives us the opportunity to conclude that they play a key role in the development of our national, legal, political thought and are a kind of value ra-diating patriotism.
Keywords: Law; state